Contractual Liability for the Property Fire in The Event of a Sole Tenant - Mohammed Ashraf Sheikho (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The Syrian legislator dealt with the case of the destruction of the leased property due to the fire when the tenant of this property is one person in the first paragraph of Article 552 of the Syrian Civil Code, which states that “1- the tenant is liable for the fire of the leased property unless he proves that the cause was beyond his control.” Accordingly, if a fire breaks out in the leased property, the tenant is liable, but the question arises about the time of comencing this liability, and the extent of liablity for the fire in case of sole tenant is differ from its extent if caused by joint tenants, and since the event of the fire bears tenant the liability, by its merits, this raises the question of misuse of the leased property, as it represents a breach of the tenant's obligation to look after the leased property. Thus, I have examined these aspects in two sections; each divided into two sub-sections. At the end, I have reached a number of conclusions and recommendations, the most important of which is that I have recommended that the Iraqi legislator to add a text to the Iraqi civil Code regarding the liability of the tenant for the fire of the leased property, and not to leave the matter to be subject to the general rules on the grounds that the fire, although it is a type of damage, but it involves a great danger. Which needs a special attention.